STATUS KONSERVASI DAN PERTUMBUHAN IKAN HIU DAN PARI YANG DIDARATKAN DI LABUHAN MARINGGAI, LAMPUNG TIMUR - Indra Gumay Yudha; Fhara Rahma Salsabilla; Sulistiono Sulistiono; Rachmad Caesario (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Shark and ray populations have declined in the wild due to overfishing and were exacerbated by low capacity of reproduction relatively, which is feared may extinction. This study aims to inventory and determine the conservation status of sharks and rays species landed at Labuhan Maringgai Fishing Port, East Lampung, and to assess the growth parameter of these fishes. The conservation status used referred to national regulations, IUCN, and CITES, while the growth study included length distribution, length-weight relationship, growth pattern, and condition factor. The number of samples analyzed 511, consisting of 157 sharks and 354 rays. The results showed that there were at least 6 species of sharks and 13 species of rays. All species of the sharks and rays were not protected under national regulations, but some of them had already listed as critically (CR), endangered (EN), and vulnerable (VU) according to the IUCN Red List. The growth pattern of the sharks varied between isometric and allometric, while most rays had negatively allometric growth pattern.